The olivo-cerebellar system: a key to understanding the functional significance of intrinsic oscillatory brain properties - Llinas, Rodolfo R. (Frontiers in Neural Circuits, 2014)
The reflexological view of brain function (Sherrington 1906) has played a crucial role in defining both the nature of connectivity and the role of the synaptic interactions among neuronal circuits. One implicit assumption of this view, however, has been that CNS function is fundamentally driven by sensory input. This view was questioned as early as the beginning of the last century when a possible role for intrinsic activity in CNS function was proposed by Thomas Graham Brow (Brown 1911; Brown 1914). However, little progress was made in addressing intrinsic neuronal properties in vertebrates until the discovery of calcium conductances in vertebrate central neurons leading dendritic electroresponsiveness (Llinas and Hess 1976, Llinas and Sugimori 1980a and b) and subthreshold neuronal oscillation in mammalian inferior olive (IO) neurons (Llinas and Yarom 1981; Llinas and Yarom 1981).This happened in parallel with a similar set of findings concerning invertebrate neuronal system (Marder and Bucher 2001). The generalization into a more global view of intrinsic rhythmicity, at forebrain level, occurred initially with the demonstration that the thalamus has similar oscillatory properties (Llinas and Jahnsen 1982) and the ionic properties responsible for some oscillatory activity were, in fact, similar to those in the IO (Jahnsen and Llinas 1984; Llinas 1988). Thus lending support to the view that not only motricity, but cognitive properties, are organized as coherent oscillatory states (Pare, deCurtis et al. 1992; Singer 1993; Hardcastle 1997; Llinas, Ribary et al. 1998; Varela, Lachaux et al. 2001).